2011
DOI: 10.1152/ajpregu.00498.2010
|View full text |Cite
|
Sign up to set email alerts
|

PDH activation during in vitro muscle contractions in PDH kinase 2 knockout mice: effect of PDH kinase 1 compensation

Abstract: Dunford EC, Herbst EA, Jeoung NH, Gittings W, Inglis JG, Vandenboom R, LeBlanc PJ, Harris RA, Peters SJ. PDH activation during in vitro muscle contractions in PDH kinase 2 knockout mice: effect of PDH kinase 1 compensation. Am J Physiol Regul Integr Comp Physiol 300: R1487-R1493, 2011. First published March 16, 2011 doi:10.1152/ajpregu.00498.2010.-Pyruvate dehydrogenase (PDH) plays an important role in regulating carbohydrate oxidation in skeletal muscle. PDH is deactivated by a set of PDH kinases (PDK1, PDK2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…To investigate this possibility, we compared our data with previous data from our lab in fed WT mice that underwent the same experimental protocol (Dunford et al 2011). Comparing these groups offers three levels of PDK4 content: basal (fed WT), elevated (fasted WT), and absent (PDK4-KO) (Wu et al 1999;Jeoung et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate this possibility, we compared our data with previous data from our lab in fed WT mice that underwent the same experimental protocol (Dunford et al 2011). Comparing these groups offers three levels of PDK4 content: basal (fed WT), elevated (fasted WT), and absent (PDK4-KO) (Wu et al 1999;Jeoung et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Our lab has previously shown that an inability to sufficiently activate PDHa during muscle contraction leads to a decrease in muscle force production at 40 Hz (Dunford et al 2011), which could suggest that the rate of muscle glucose oxidation may limit the ability of muscle to produce higher forces. This is supported by previous research in single mouse flexor brevis muscle fibres that demonstrated muscle fatigue during contraction occurred with a reduced availability of glucose, even in the absence of any measurable changes in muscle viability (Allen et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pyruvate dehydrogenase complex (PDC) having a predominant role in the regulation of mammalian metabolism represents the point-of-no-return regarding the utilization of carbohydrate, plays a leading role in maintaining glucose homoeostasis and is immensely involved in the metabolic pathway required for energy production and movement [1][2][3]. PDC is entirely nuclear encoded and consists of multiple copies of three structurally distinct, but functionally interdependent, enzymes (E 1 through E 3 ) [4].…”
Section: Introductionmentioning
confidence: 99%